2022
DOI: 10.1021/acsami.2c14153
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Aqueous Zinc-Ion Batteries Enabled by Binder-Free and Ultrathin V2O5–x@Graphene Aerogels with Intercalation Pseudocapacitance

Abstract: As a result of the absence of solid-state diffusion limitation, intercalation pseudocapacitance behavior is emerging as an attractive charge-storage mechanism that can greatly facilitate the ion kinetics to boost the rate capability and cycle stability of batteries; however, related research in the field of zinc-ion batteries (ZIBs) is still in the initial stage and only found in limited cathode materials. In this study, a novel V 2 O 5−x @rGO hybrid aerogel consisting of ultrathin V 2 O 5 nanosheets (∼1.26 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 81 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…VOH@PEDOT has a wider conduction band, with the Fermi level moving through it, indicating that more electronic states can be used for the electronic transmission, resulting in higher conductivity than VOH. 35 The C 2p and V 2p orbitals overlap with the O 2p orbital near the Fermi level (Fig. 6d and S8 †), indicating orbital hybridization and stable bonding of C and V with the O atom.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…VOH@PEDOT has a wider conduction band, with the Fermi level moving through it, indicating that more electronic states can be used for the electronic transmission, resulting in higher conductivity than VOH. 35 The C 2p and V 2p orbitals overlap with the O 2p orbital near the Fermi level (Fig. 6d and S8 †), indicating orbital hybridization and stable bonding of C and V with the O atom.…”
Section: Resultsmentioning
confidence: 95%
“…recognized as promising shell materials to improve both the stability and conductivity. For instance, Chen et al 35 reported a V 2 O 5− x @reduced graphene oxide (rGO) hybrid aerogel with a three-dimensional rGO network used as a freestanding cathode for AZIBs. As expected, the V 2 O 5− x @rGO cathode showed 153.9 mA h g −1 at 15 A g −1 and 90.6% capacity remained after 1050 cycles at 0.5 A g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…For the high resolution XPS spectrum of V 2p, the electron binding energies of V 2p1/2 and V 2p3/2 were 524.95 and 517.35 eV, respectively, and the distance of the peak is 7.6 eV, manifesting that the vanadium atom is +5. 4 Moreover, the peaks of 523.7 and 516.1 eV ascribed to +4 valence vanadium V 2p1/2 and V 2p3/2, respectively, 19 were also detected, indicating the presence of defect sites in the supported catalyst, which is helpful to improve the catalytic oxidation desulfurization performance. 20,21 In order to analyze the morphology and structure of 30% V 2 O 5 /3D g-C 3 N 4 , SEM and TEM analyses are shown in Figure 2.…”
mentioning
confidence: 99%
“…A special storage mechanism of intercalation pseudo-capacitance is identified for VOH. 7 Although its relatively low average operating potential (2–4 V vs. K + /K) would set a limitation on the energy density, it can deliver a discharge capacity of 110 mA h g −1 at 10 mA g −1 with an excellent capacity retention of 99.2% even after 700 cycles at 500 mA g −1 .…”
mentioning
confidence: 99%
“…On the basis of the above results, the intercalation pseudo-capacitance mechanism of the VOH-S cathode is proposed, which emphasizes that ions migrate inside crystal lattices, especially moving between the layers, rather than the surfaces. 7 Intercalation pseudocapacitive electrodes usually contain sufficient interstitial ion pathways and present no phase transformations during the charge and discharge processes. 31 Considering the solid-solution reaction, ultra-large 2D ion diffusion pathways, superior reaction kinetics, and fast capacitive-dominated characteristics, it is rational to deduce an intercalation pseudocapacitive behavior for VOH-S.…”
mentioning
confidence: 99%